2011
DOI: 10.1063/1.3549704
|View full text |Cite
|
Sign up to set email alerts
|

Fast magnetization precession observed in L1-FePt epitaxial thin film

Abstract: Fast magnetization precession is observed in L10-FePt alloy epitaxial thin films excited and detected by all-optical means. The precession frequency varies from 45 to 65 GHz depending on the applied magnetic field strength and direction, which can be explained by a uniform precession model taking account of first- and second-order uniaxial magnetic anisotropy. The lowest effective Gilbert damping constant has a minimum value of 0.055, which is about half that in Co/Pt multilayers and is comparable to Ni/Co mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 22 publications
1
100
3
1
Order By: Relevance
“…5, corresponding to 0 ≤ S ≤ 0.985, are appreciably smaller than the measured one which amounts to α ≈ 0.06 reported for a thin L1 0 FePt epitaxial film. 54 The high measured value of α might be thus explained by the present calculations by assuming a very small concentration of antisites in the prepared films, which does not seem too realistic. Another potential source of the discrepancy lies in the thin-film geometry used in the experiment.…”
Section: Fept Alloys With a Partial Long-range Ordermentioning
confidence: 81%
“…5, corresponding to 0 ≤ S ≤ 0.985, are appreciably smaller than the measured one which amounts to α ≈ 0.06 reported for a thin L1 0 FePt epitaxial film. 54 The high measured value of α might be thus explained by the present calculations by assuming a very small concentration of antisites in the prepared films, which does not seem too realistic. Another potential source of the discrepancy lies in the thin-film geometry used in the experiment.…”
Section: Fept Alloys With a Partial Long-range Ordermentioning
confidence: 81%
“…The question is still open whether the well developed theories can shed light on the damping behavior in such materials, and therefore motivates extensive research [31,[38][39][40][41][42][43]. For instance, S. Mizukami et al demonstrated a low value of α 0 with considerable K u in MnGa alloys, due to the low density of states at the Fermi level, D(E F ) [40].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Similar relatively high values for the intrinsic Gilbert damping parameter were reported on continuous FePt films with lower magnetocrystalline anisotropy. [21][22][23] In summary, our here presented results show that coherent spin precession can be excited in a highly anisotropic, granular L1 0 FePt films using ultrashort light pulses of 100 fs. The high anisotropy fields up to more than 10 T found in the here investigated sample lead to FMR frequencies in the THz range.…”
mentioning
confidence: 99%